Implementing the Geogebra Applet-Based Connecting, Organizing, Reflecting, Extending (CORE) Learning Model for Students' Critical Thinking Ability in Learning Styles - Ardiyanto, Bagas; ‘Adna, Syita Fatih; Chasanah, Aprilia Nurul (Pendidikan Matematika STKIP Kusuma Negara, 2022)
In the era of globalization, the 21st century requires learning integrated with technological developments and innovation. This study aims to analyze the implementation of the Connecting, Organizing, Reflecting, Extending (CORE) learning model based on the Geogebra Applet on students' critical thinking ability regarding learning styles. The design of this study is quasi-experimental. The samples in this study were students of class XI MIPA 1 and XI MIPA 2 SMA Negeri 2 Magelang who were selected by the cluster random sampling technique. The instruments used in this study were critical thinking ability tests and learning style questionnaires. Based on the results of the hypothesis test conducted with the ANOVA test of two unequal cell paths and the LSD (Least Significance Difference) follow-up test, results were obtained: (i) The Core learning model based on the Geogebra Applet produces students' critical thinking ability better than the direct learning model; (ii) There are differences in critical thinking ability between students and the learning styles of divergers, convergers, assimilators and accommodators; (iii) There is no interaction between the Geogebra Applet-based CORE learning model and the direct learning model with the student's learning style.